Typification and factors associated with violence among the homeless in a municipality of Minas Gerais, Brazil - de Oliveira, Gislaine Cristina Moraes; Martins, Ananda Carvalho; Pazini, Débora de Sousa; De Paula, Eloisa Elena Paschoalinotte [UNESP]; Nunes, Lélia Cápua; de Freitas, Eulilian Dias (FapUNIFESP (SciELO), 2023)
The scope of the study was to typify the violence suffered by the homeless population and analyze the associated factors in a medium-sized municipality in Minas Gerais. A cross-sectional study was conducted and data about sociode-mographic status, health, risk behaviors and occurrence of violence among the homeless was collected. Multivariate logistic regression was performed to verify the association between exposure and outcomes. Of the 85 respondents, the majority were male (75.3%), aged between 40 and 59 years (59.5%), non-white (86.3%), smok-ers (69.4%), alcoholics (80.7%) and drug users (53.6%). The overall prevalence of violence was 62.3%. The types of violence most reported were verbal and physical aggression and threats. Being a woman (OR 42.1; 95%CI 27.8-638.0) and being non-white (OR 9.02; 95%CI 1.33-61.1) were associated with a higher risk of experiencing vi-olence. Having no morbidity (OR 0.14; 95%CI 0.03-0.62) and living on the streets for up to five years (OR 0.17; 95%CI 0.04-0.71) revealed a neg-ative association. It was observed how violence is present in the urban context associated with sex, race, self-reported morbidity and time living on the streets.
Tipificação e fatores associados à ocorrência de violência em pessoas em situação de rua em um município de Minas Gerais, Brasil
Keywords: Exposure to violence; Homeless people; Violence